Parametric Equalizer Improves Baxandall Tone Control - Malvar, Henrique S. (Electronics, 1981)
Simple active filters are used here to build a continuously-adjustable parametric equalizer having the same general response as the popular Baxandall circuit, which uses a switch-selectable scheme for bass and treble equalization.